RETELLING FOLKLORE IN THE 21ST CENTURY CHILDREN’S LITERATURE: A COMPARATIVE STUDY ON CHILDREN’S BOOK SERIES BY OKKY MADASARI AND DANIEL PINKWATER - Jatmiko, Rahmawan (Rubikon : Journal of Transnational American Studies, 2025)
This study searches out, observes, and analyzes the elements of folklore in the children’s book series by two authors with different cultural backgrounds: Indonesian background and American background. For the analysis of the Indonesian author’s works, this study chooses the adventure series of a child named Matara, a.k.a. Mata, written by Okky Madasari, an Indonesian writer who was previously known as a writer of literary works that are quite idealistic. From her Mata adventure series, this research discusses three works, namely the series Mata Di Tanah Melus (2018), Mata dan Rahasia Pulau Gapi (2019), and Mata dan Manusia Laut (2019). For the work of the American writer, this study selects Daniel Pinkwater’s children’s book, Beautiful Yetta: The Yiddish Chicken (2010). All the works discussed in this paper are works of 21st-century children’s literature, the results of which are expected to provide new insights into the repertoire of children’s literature studies, especially those related to Indonesian and American children’s literature. The study of these works found that the forms of elements of culture and folklore can be used to convey social criticism to certain parties. In this case, there is society and authority. Above all, this study underlines that there are distinct presentations of those criticisms that utilize myths, folklore, and cultural symbols by Indonesian and American children’s book authors.